Mother’s Knowledge And Husband Support On Using Long Term Contraceptive Method In Lolang Public Health Center, Manggarai Regency - Reineldis Elsidianastika Trisnawati; Makrina S Manggul; Putriatri K Senudin; Dionesia O Laput; Silvia A Halu; Eufrasia P Padeng; Fransiska N Nanur (Universitas Islam Lamongan, 2021)
In order to achieve the controlled and managed population growth, government launched a Family Planning Program for Reproductive Age Couples. Within the program, the use of long term contraceptive method is the most effective measure for the Family Planning. Based on WHO data in 2017, 58% of reproductive age couple choose modern contraceptive method, greater than traditional method which were around 5%. In Lolang Public Health Center, the number of long term contraceptive method user is as much as 17,02% and non-long term contraceptive method user is as much as 82,8%. These data indicates that the majority of contraceptive method used by reproductive age couple is non-long term contraceptive method. This study aims to analyze the relationship between mother’s knowledge and husband’s support on using long term contraceptive method in Lolang Public Health Center, Manggarai Regency. This study is a descriptive correlational study using cross sectional design. The sampling method using simple random sampling with 101 respondents. The independent variables in this study are mother’s knowledge and husband’s support and the dependent variable is the use of lon term contraceptive method. Data analysis conducted univariately and bivariately using chi square test (α=0,05). The study result indicates that the majority of respondents have poor knowledge as much as 64,4% with p value 0.001 and unsupported by the husband to use long term contraceptive method as much as sebesar 58,4% with p value 0.000. Based on this study, it is concluded that there is a significant correlation between mother’s knowledge and husband’s support toward the use of contraceptive methods within the Family Planning program.